Phylogenetic analysis of mitochondrial D-loop sequence of Mongolian wild boars - Khamit, Ali; Bayarlkhagva, Munkhjargal; Bazarsad, Davaa; Ulziibat, Bolortuya; Damdin, Bayarlkhagva; Gun-Aajav, Bayarmaa (Proceedings of the Mongolian Academy of Sciences, 2022)
Genomic DNA was extracted from tissue specimens of wild boars (Sus scrofa) in 10 different locations Mongolia. D-loop part of genome was amplified by PCR and was subjected to DNA sequencing. Determined sequences from 18 specimens were registered with the GenBank and accession numbers were obtained. A total of 54 complete mitochondrial D-loop sequences of wild boars available with NCBI GenBank were taken as a reference for comparison with that of Mongolian wild boars. Sequence alignment, detection of parsimonious informative sites, model selection, calculation of nucleotide distances, and Maximum Likelihood (ML) phylogenetic tree construction with 1000 bootstrapped replications were conducted using MEGA X software. Maximum Likelihood trees were constructed by the Hasegawa-Kishino-Yano (HKY) model. The results of the study showed that geographic location played an important role in sequence divergence between wild boars from various locations. Most of them were grouped together according to their respective geographic locations, except for several individuals. It is highly likely that the Mongolian subpopulation of wild boars, such as S. scrofa raddianus and S. scrofa nigripes, have had the same ancestor. In order to fully evaluate the distribution, ecology, and biology of Mongolian wild boars, it is essential to compare supplemental gene sequences that can reveal phylogenetic differences from the populations in the neighboring areas, such as Russia, northeast China, and Kazakhstan. The results of this study will be useful and informative for the protecting and conserving of wild boars in Mongolia.